Bioactivities of Some Wild Fruits Grown in Turkey - Sagdic, Osman; Polat, Busra; Yetim, Hasan (SPRINGER, 2022)
In this study some bioactive properties of extracts of wild pear (Pyrus elaegnifolia), hawthorn (Crataegus spp.), oriental hackberry (Celtis tournefortii), oleaster (Elaeagnus angustifolia), Japanese crabapple (Malus floribunda), rosehip (Rosa canina), pedunculate oak (Quercus robur), service tree (Sorbus domestica) and firethorn (Pyracantha coccinea) wildly growing in Turkey were investigated. The fruit extracts were analysed in terms of total phenolic content (TPC), antioxidant activities (DPPH and phosphomolybdenum methods) and antimicrobial activity. In the results, TPC, IC50 value of DPPH and IC50 value of phosphomolybdenum for pedunculate oak were 454.35 mg GAE/g d.w., 340.52 mg AAE/g d.w. and 96.52%, respectively. Service tree and firethorn exhibited the lowest TPC (4.11 mg GAE/g d.w.) and IC50 value of DPPH (53.32 mg AAE/g d.w.), respectively. Moreover, antimicrobial activity of oleaster was 2.46%. The hackberry fruit extract had no inhibitory effect against the tested microorganisms whereas pedunculate oak extract (with 10%) had the highest inhibitory effect against Aeromonas hydrophila. Additionally, all the fruit extracts had no antimicrobial activity against the Saccharomyces cerevisiae. In conclusion, wild edible fruit extracts can be used as bioactive material due to their antioxidant and antimicrobial activity in food industry and human nutrition.
Keywords: Total phenolic content; Antioxidant; Antimicrobial; Wild fruits; PHENOLIC-COMPOUNDS; ANTIMICROBIAL PROPERTIES; ANTIOXIDANT ACTIVITY; HAWTHORN; EXTRACTS; PLANTS; Agriculture